PERSEPSI WARGA BELAJAR TERHADAP PELAKSANAAN PEMBELAJARAN KETERAMPILAN TATA RIAS DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI, PEKANBARU - Gusmarni, Reflia; Jas, Jasfar; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the perception of learning on the implementation of makeup learning in Panti Sosial Bina Remaja (PSBR) Rumba, Pekanbaru. This research is descriptive with quantitative approach. The research was done in the Panti Sosial Bina Remaja (PSBR) Rumbai, Pekanbaru. The population in this study was 72 people. The research sample was 42 people and the trial sample was20 people, with a critical level of 10%. The sample used was simple random sampling technique. Data were analyzed with descriptive quantitative techniques in the form of a percentage. The results showed that the perception of the learners on the implementation of the learning skills of make up in Panti Sosial Bina Remaja (PBSR) Rumbai, Pekanbaru quite well, judging from the indicator (1) Input obtained percentage value could not agree by 36%, agreed by 40%, less agree 15% disagree 4% and strongly disagree 5%, and then (2) Process obtained percentage value could not agree by 28%, agreed by 47%, less agreed by 13%, disagree 6 and strongly disagree 6 %. And (3) Output values obtained percentage of 38% strongly agree, 41% agree, 15% disagree, disagree 3% and 3% strongly disagree. Thus the most best output indicator, which has an average value of percentage of 79% means that people learn after graduation in their PSBR have independent business and improve the quality of education.Key words: Perception, Learning Implementation, Skills Makeup